TCC in Transplant Ureter—When and When Not to Preserve the Transplant Kidney. (5th January 2016) - Olsburgh, J.; Zakri, R. H.; Horsfield, C.; Collins, R.; Fairweather, J.; O'Donnell, P.; Koffman, G.
Abstract : We present four cases of transitional cell carcinoma of the transplant ureter (TCCtu). In three cases, localized tumor resection and a variety of reconstructive techniques were possible. Transplant nephrectomy with cystectomy was performed as a secondary treatment in one locally excised case. Transplant nephroureterectomy was performed as primary treatment in one case. The role of oncogenic viruses and genetic fingerprinting to determine the origin of TCCtu are described. Our cases and a systematic literature review illustrate the surgical, nephrological, and oncological challenges of this uncommon but important condition.